Macroscopic Analysis Of The Viscous-Diffusive Traffic Flow Model - Gabriel Obed Fosu; Albert Adu-Sackey; Joseph Ackora-Prah (Mathematics in Applied Sciences and Engineering, 2022)
Second-order macroscopic traffic models are characterized by a continuity equation and an acceleration equation. Convection, anticipation, relaxation, diffusion, and viscosity are the predominant features of the different classes of the acceleration equation. As a unique approach, this paper presents a new macro-model that accounts for all these dynamic speed quantities. This is done to determine the collective role of these traffic quantities in macroscopic modeling. The proposed model is solved numerically to explain some phenomena of a multilane traffic flow.  It also includes a linear stability analysis. Furthermore, the evolution of speed and density wave profiles are presented under the perturbation of some parameters.